Legal Certainty, Institutional Capacity, And Social Utility: Reassessing Indonesia’s Waqf Law in Advancing Productive Waqf Incubation - Slamet Slamet; Mochammad Arifin (Sakina: Journal of Family Studies, 2026)
Waqf is an Islamic philanthropic institution that has historically played an important role in supporting social welfare and economic development in Muslim societies. In Indonesia, the increasing demand for productive and sustainable waqf management has encouraged the modernization of the legal framework and governance of waqf. This study aims to analyze the progressiveness of the national waqf legal framework in supporting the development of productive waqf, particularly through the nazhir incubation program. The focus of the study is directed at Law Number 41 of 2004 concerning Waqf and Government Regulation Number 42 of 2006 as the primary legal foundations governing waqf management in Indonesia. To date, there remain limited studies that specifically assess whether these regulations adequately provide a legal framework for institutionalizing nazhir incubation programs as a mechanism to enhance the professionalism of waqf managers. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that although waqf regulations have provided a legal basis for the development of productive waqf, their effectiveness still faces several challenges. These include a normative gap reflected in the absence of explicit regulation concerning nazhir incubation, an institutional gap caused by weak coordination among waqf-related institutions, and a human resource gap related to limited professionalism and managerial capacity of nazhirs. Therefore, strengthening regulatory frameworks and institutionalizing nazhir incubation programs are strategic steps to enhance the effectiveness of productive waqf management in Indonesia.